Sistem Akuntansi dan Anggaran Berbasis Kinerja Dalam Mewujudkan Akuntabilitas Pemerintah Daerah di Kabupaten Aceh Barat Daya - Hafiza, Hafiza; Sartika, Dewi; Marlina, Lilis (Universitas Teuku Umar, 2025)
This study examines the effects of the Government Accounting System, Clarity of Budget Targets, and Performance-Based Budgeting on the Accountability of Government Agency Performance (AKIP) in the Department of Agriculture and Food, Southwest Aceh Regency. Using purposive sampling, 35 employees directly involved in budgeting processes were selected as respondents. Data were analyzed using multiple linear regression. The results show that the Government Accounting System, Clarity of Budget Targets, and Performance-Based Budgeting each have a significant positive effect on AKIP. Simultaneously, these three variables also influence AKIP, indicating that effective accounting practices, clear budget objectives, and performance-oriented budgeting collectively enhance government performance accountability. Future studies are encouraged to include additional variables, broader samples, and different methods to strengthen generalizability.